Nucleotide sequence of the gene for a fibronectin-binding protein from Staphylococcus aureus: use of this peptide sequence in the synthesis of biologically active peptides. - Signäs, C (1989)
Binding of cells of Staphylococcus aureus to fibronectin, which may represent a mechanism of host tissue adherence, involves a fibronectin-receptor protein present on the bacterial surface. Cloning of a gene coding for a staphylococcal fibronectin-binding protein and construction of a fusion protein with fibronectin-binding properties was previously reported from our laboratory. We have now sequenced the gene and deduced a primary sequence of the fibronectin-binding protein. The protein resembles other cell-wall-associated proteins on Gram-positive bacteria in that it (i) appears to be anchored in the cell membrane via its C-terminal end, (ii) contains a proline-rich repeating unit outside the membrane anchor, and (iii) contains a long (36-amino acid) signal sequence at the N terminus. The fibronectin-binding activity has been localized to a domain composed of a 38-amino acid unit repeated completely three times and partially a fourth time; the identity between the three 38-amino acid sequences varies from 42 to 87%. Three synthetic peptides mimicking the structure of each 38-amino acid unit were constructed. All three peptides interacted with fibronectin, as indicated by their ability to inhibit binding of fibronectin to staphylococcal cells, whereas an unrelated 37-amino acid peptide showed no inhibitory activity.